QARAQALPAQ TILINDEGI FIZIKA ATAMALARÍNÍŃ QOLLANÍLÍW ÓZGESHELIGI - Qarlıbaeva, G.; Asanova, D. (ILIM hám JÁMIYET, 2022)
The article provides information on the terminology of the Karakalpak language, as well as physical terms. It has been learned that the terms of physics are used figuratively in the language of fiction. The properties of the terms are analyzed related to physical science.